Dampak Penggunaan Smartphone Terhadap Perkembangan Kognitif Anak Usia Dini (Studi Pada Desa Kunduran) - Ermanti Lubis, Riyani; Junia Restika, Anggi (Yayasan Darussalam Bengkulu, 2024)
This journal was created with the aim of finding out the impact of smartphone use on early childhood development. As we know, communication technology in this era is developing very rapidly. Almost all groups, including adults, students and young children, have used it. The method for preparing this article is a qualitative method. Data was obtained through observations of early childhood in Kunduran village, East Seluma subdistrict, Seluma district. Theoretically, it is hoped that this journal can become a reference to increase the knowledge of early childhood education to the public in the context of understanding problems regarding the impact of smartphone use in early childhood. Based on the facts in the field, some parents use smartphones as a shortcut when accompanying their children. So that parents can carry out their activities in peace, without worrying that their children will wander off, play dirty, mess up the house, which will ultimately make them fussy and disturb their parents. Parents are expected to be more careful in supervising and monitoring their children's daily activities in using smartphones to minimize the negative side that arises from smartphone use, and smartphones should be used and utilized for positive things. The use of smartphones should not be given to children under 8 years of age, because at that age it is better for children to be directed into activities that have activities in the environment so that it is easy for them to socialize.